K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 8 2020

\(C=\frac{\cos4x.\tan2x-\sin4x}{\cos4x.\cot2x+\sin4x}\)

\(=\frac{\cos4x.\sin2x-\sin4x.\cos2x}{\cos4x.\cos2x+\sin4x.\sin2x}.\frac{\sin2x}{\cos2x}\)

\(=\frac{\sin\left(2x-4x\right)}{\cos\left(4x-2x\right)}.\frac{\sin2x}{\cos2x}=-\frac{\sin^22x}{\cos^22x}=-\tan^22x\)

5 tháng 3 2019

Chọn C.

Ta có

C = [ ( sin2x + cos2x) – sin2cos2x]2 - [ ( sin4x + cos4x) 2 - 2sin4x.cos4x]

= 2[ 1-sin2x.cos2x]2 - [ ( sin2x + cos2x) 2 - 2sin2x.cos2x]2 + 2sin4x.cos4x

= 2[ 1-sin2x.cos2x]2 - [1-sin2x.cos2x]2 + 2sin4x.cos4x

= 2( 1 - 2sin2x.cos2x + sin4x.cos4x)- ( 1 - 4sin2xcos2x + 4sin4x.cos4x) + 2sin4x.cos4x

= 1.

NV
28 tháng 4 2021

\(=\dfrac{1}{2}sin6x-\dfrac{1}{2}sin2x-\left(\dfrac{1}{2}sin4x-\dfrac{1}{2}sin2x\right)\)

\(=\dfrac{1}{2}sin6x-\dfrac{1}{2}sin4x\)

\(=cos5x.sinx\)

11 tháng 5 2022

gt rõ hơn được không ạ, e k hiểu lắm ạ

2 tháng 7 2018

Chọn C.

Ta có: C = 2( sin4x + cos4x + sin2x.cos2x) 2 - ( sin8x + cos8x)

= 2 [ (sin2x + cos2x) 2 - sin2x.cos2x]2 - [ (sin4x + cos4x)2 - 2sin4x.cos4x]

= 2[ 1 - sin2x.cos2x]2 - [ (sin2x+ cos2x) 2 - 2sin2x.cos2x]2 + 2sin4x.cos4x

= 2[ 1- sin2x.cos2x]2 - [ 1 - 2sin2x.cos2x]2  + 2sin4x.cos4x

= 2( 1 - 2sin2xcos2x+ sin4x.cos4x) –( 1- 4sin2xcos2x+ 4sin4xcos4x) + 2sin4x.cos4x

=  1.

16 tháng 11 2018

9 tháng 8 2019

\(D=\frac{1+sin2x+cos2x}{1+sin2x-cos2x}=\frac{1+2sinxcosx+2cos^2x-1}{1+2sinxcosx-1+2sin^2x}\)

\(D=\frac{cosx\left(sinx+cosx\right)}{sinx\left(sinx+cosx\right)}=cotx\)

9 tháng 8 2019

\(F=\frac{sinx+sin4x+sin7x}{cosx+cos4x+cos7x}\)

\(F=\frac{2sin4xcos3x+sin4x}{2cos4xcos3x+cos4x}\)

\(F=\frac{2sin4x\left(cos3x+1\right)}{2cos4x\left(cos3x+1\right)}=tan4x\)

2 tháng 5 2021

undefined

27 tháng 4 2017

Hỏi đáp Toán

14 tháng 6 2020

\(D=\frac{sin4x+sin5x+sin6x}{cos4x+cos5x+cos6x}\)

\(=\frac{\left(sin4x+sin6x\right)+sin5x}{\left(cos4x+cos6x\right)+cos5x}\)

\(=\frac{2sin\frac{4x+6x}{2}.cos\frac{4x-6x}{2}+sin5x}{2cos\frac{4x+6x}{2}.cos\frac{4x-6x}{2}+cos5x}\)

\(=\frac{2sin5x.cos\left(-x\right)+sin5x}{2cos5x.cos\left(-x\right)+cos5x}=\frac{sin5x\left(2.cos\left(-x\right)+1\right)}{cos5x\left(2.cos\left(-x\right)+1\right)}=\frac{sin5x}{cos5x}=tan5x\)